Sistem Terintegrasi Berbasis Web untuk Pencarian dan Pemesanan Kelompok Seni Pertunjukan - Erliyah Nurul Jannah; Ainul Hidayah; Mas’ud (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Performance art group is a group of people who are experts in the particular art and usually invited to perform their artistic skills. Each region has tens or even hundreds of performance art groups. Communities run into problems in finding and booking the art group because the information of local art groups is not published effectively. A web based information system for searching and booking the performance art group is one of the solutions. The system is developed based on Waterfall model through four steps, which are analyzing, designing, implementation, and testing. The system is built by using PHP as the programming language and MySQL as Database Management System (DBMS). The existing features of the proposed system is performance art group registration, searching, and booking. This system makes the process of finding and booking can be done more efficiently in which people do not need to come directly to the address of the owner of an art group.